(3GdeMUd TQM GdeaUds - (3YHO Gddg Hf GdMSjf Hf YHO Gddg GdYcHQj GdHZOGOj, CHh GdHbGA, eMH GdOjf,J (B616 (3g` s; (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3Ke de CRd CLhH Hg GdHdGO Edi Cf XaQJ HMVQI ehdGfG CHj GdeXaQ YHSi Hf Gdedc GdYGOd CHj HcQ Hf CjhH fUjQ CejQ GdeDefjf s
(3BNQgG (B:s
(3bhdg JYGdi WGYI hbhd eYQha LYdgG eHJOC hHGLedI aGdeWdhH hgh GdaGFOI efgeG BNQ GdeLdO GdChd ef GdeMUd ai TQM GdeaUd s
(3HChdg GdYOjO ef GdJedcGJs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1774s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs